Furniture in traditional Malay Houses of Melaka [electronic resource] - Nabilah Zainal Abidin, 1989-; Fawazul Khsir Ibrahim, supervisor; Raja Nafida Raja Shahminan, supervisor; Fakulti Alam Bina (2015)
Thesis (Sarjana Senibina)) - Universiti Teknologi Malaysia, 2015